An interesting synthesis on the evolution of plant pollination by birds (Avocetta, 2025)
Review of Ollerton J. 2024. Birds & Flowers. An Intimate 50 Million Year Relationship. Pelagic Publishing, London. 312 pp., 28 color plates.